(untitled) (Journal of International Studies, 2014)
This paper investigates the benefits of investing in REITs in the context of multi-period portfolio choice and dynamic asset allocation using the methodology of Campbell et al. (2003). We compute the total and intertemporal hedging demand for REITs by solving the multi-period asset allocation problem for an investor with an infinite horizon and Epstein-Zin utility, and then compare the utility benefits improved by adding REITs in an existing portfolio. Our results document significantly sizable mean total and intertemporal hedging demands for REITs. Furthermore, these demands are relatively stable and permanent in magnitude under various settings of intertemporal substitution and the relative risk aversion. Furthermore, we find that the investment benefits improved by REITs are considerable, and far more suitable for conservative investors with relatively high risk aversion.